Optimal heat rejection pressure of CO2 heat pump water heaters based on pinch point analysis - Chen, Yun-Guang (International journal of refrigeration, 2019)
•The pinch effect considerably affects the optimal heat rejection pressure.•The optimal heat rejection pressure was underestimated by the commonly used model.•A new correlation of optimal pressure is proposed for CO2 heat pump water heaters. The control of heat rejection pressure is of great importance for transcritical CO2 heat pump water heaters. However, almost all the existing correlations of optimal heat rejection pressure are based on an assumption of constant CO2 exit temperature from gas cooler when changing the high-side pressure. Actually, pinch effect occurring in CO2 gas cooler would have great impacts on CO2 exit temperature as the high-side pressure varies, which in turn affects overall system performance. A cycle simulation model was developed in the present study incorporating pinch point analysis for gas cooling process. The model is independent on heat exchanger geometry parameters, which guarantees the generality of the model. Sensitivity analyses of main impact factors were conducted in detail including inlet and outlet water temperature, refrigerant evaporation temperature and superheat degree, pinch temperature difference and isentropic efficiency of compressor. Furthermore, a new correlation of optimal heat rejection pressure was proposed.